P54 CPAP compliance and symptomatic benefit: a comparison of patients established on CPAP from GP or preoperative screening. (December 2018) - Oakham, EJ; Unstead, M; McGown, AD
Abstract : Introduction: Presence of OSA can have implications in the perioperative and postoperative period and preoperative screening (POS) is recommended (Gross et al. Anesthesiology 2014;120(2):268–86). In our institution, patients are screened using the STOP-Bang questionnaire. Elective surgery may be postponed if overnight oximetry shows an Oxygen Desaturation Index (ODI)≥20. Patients diagnosed with OSA from POS are often asymptomatic. We sought to determine whether there was a difference in compliance and symptomatic benefit between patients commenced on CPAP as a result of a GP referral and as a result of POS. Methods: Over the period January – December 2017, 96 consecutive patients referred from a GP and 64 consecutive patients referred from POS with ODI≥20 were commenced on CPAP. Patients who had not attended for review or had returned their machine were excluded. Epworth Sleepiness Score (ESS) at initiation and first review, weight, ODI, age, gender and compliance at first review were obtained retrospectively and compared based on source of original referral. Patients were judged as compliant with an average usage of ≥4 hours per night. Statistical analyses were performed using Microsoft Excel. Results: 83 GP-referred patients and 55 POS-referred patients had been reviewed. 14% of patients from both groups had not attended for review or had returned their machine. Patients referred from a GP were younger and sleepier with a higher ODI. Both groups had more males than females; however there was no difference in gender distribution between the groups. At first review, there was no difference in compliance however more symptomatic benefit was seen from GP referrals (table 1). Conclusions: Our data confirms that there is a significant difference in daytime sleepiness between patients referred from their GP and from POS (Dwarakanath et al. Thorax 2013;68(Suppl 3):A1–A220). Patients referred from their GP perceive more symptomatic benefit from CPAP therapy but are no more likely to be compliant at first review than patients diagnosed at POS. Longer term follow up would help elucidate if patients diagnosed as a result of POS remained compliant post-surgery.